TINJAUAN YURIDIS TENTANG PENGANGKATAN ANAK (ADOPSI) BERDASARKAN PENETAPAN NOMOR : 365/PDT.P/2019/ PN.MTR - NI KADEK MADAWI DWIYANTI RAHAYU; Wahyuddin Wahyuddin (Private Law, 2023)
This study aimed were to know Judge’s consideration for adoption viewed from the court’s determination and to know legal impact of the adoption according Staatblad 1917 No. 129, Islamic Law, customary law, and Government Regulation Number 54 of 2007. Legal impact of adoption according Staatblad 1917 No. 129 the relationship between child and his biological parents is separated, but in Islamic Law, adoption does not create any legal consequences. Legal impact from the perspective of customary law, adopted children continue the position of their adoptive parents, legal consequences according to government regulation No. 54 of 2007 adopted children have the same position as biological children.